Profil Pengetahuan Komunikasi Terapeutik Siswa SMK Program Keahlian Layanan Kesehatan SMK Muhammadiyah Lumajang - Agustin, Amarlian Bilqisthi; Mochamad Bruri Triyono; Wagiran (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Therapeutic communication is used by health professionals, such as doctors, nurses, or counselors, to help individuals overcome emotional, psychological, or physical problems. Therapeutic communication is an essential competency that vocational school students must have before doing practical fieldwork. This research aimed to determine the therapeutic communication knowledge profile of vocational high school students in health service expertise programs. This type of research is quantitative. The sampling technique used was a proportionate stratified random sampling of 71 people from all 238 vocational school students in health service expertise programs. Data collection was carried out quantitatively using questionnaires filled out directly by respondents. The research results show the average score based on class level, which shows that the three class levels have the same average score and are classified as not yet competent or below 70. The difference in the average score of class X to class XI and class XI to class III is insignificant. The level of therapeutic communication knowledge of 18% of students is competent, while 82% are classified as yet competent. Considering the importance of therapeutic competence for prospective health workers, it is hoped that the research results can become a reference and illustration for health vocational schools to increase competence in therapeutic communication for students.